Development of a carboxymethyl chitosan functionalized nanoemulsion formulation for increasing aqueous solubility, stability and skin permeability of astaxanthin using low-energy method. (17th November 2017) - Hong, Liang; Zhou, Chuan-Li; Chen, Feng-Ping; Han, Dan; Wang, Chun-Yuan; Li, Jia-Xin; Chi, Zhe; Liu, Chen-Guang
Abstract: In this research, firstly astaxanthin (ASX)-loaded nanoemulsions (NEs) were produced using a convenient low-energy emulsion phase inversion method. The optimised ASX-NEs were prepared in the presence of Cremophor ® EL and Labrafil ® M 1944 CS, with a surfactant-to-oil ratio of 4:6. The ASX-NE droplets were spherical with a mean droplet diameter below 100 nm and a small negative surface charge. The system was stable without alteration of mean droplet diameter for three months. Then, the ASX-NE was functionalised with carboxymethyl chitosan (CMCS) through direct CMCS (0.02%) incorporation during the preparation process. The ASX chemical stability and skin permeability increased in the following order: ASX solution control < ASX-NE < CMCS-ASX-NE. Cell viability assays on L929 cells revealed low cytotoxicity of blank NE, ASX-NE and CMCS-ASX-NE in the range from 5 to 500 μg mL −1 . In conclusion, the CMCS-ASX-NE might be a promising delivery vehicle in dermal and transdermal products.